Common Fixed Point Theorem for Minimal Commutativity Type Mappings in Fuzzy Metric Spaces: Sanjay Kumar - Team, Support (Thai Journal of Mathematics, 2008)
In this paper, we introduce the concept of R -weak commutative of type (Ag) mappings in fuzzy metric spaces akin to to concept of R -weak commutative of type (Ag) mappings in metric spaces, introduced by Pathak et al. [16] and prove common fixed point theorems for weakly compatible mappings, R-weak commutative mappings and R -weak commutative of type (Ag) mappings (we call all these mappings as minimal commutativity type mappings) which generalizes the Results of various authors present in literature.